The impact of action video game experience on visual selective attention in deaf middle school students - Cui, Ting; Ye, Dongmao; Dong, Yifan; Gong, Huina; Guo, Yuanbing; Gao, Zhi (Frontiers in Psychology, 2025)
IntroductionPrevious studies have shown that congenital deafness enhances peripheral visual processing but may reduce attention to central stimuli. In contrast, action video game experience has been shown to improve top-down attentional control and resistance to distraction. However, it remains unclear whether action video game experience can modify the peripheral attention bias typically observed in deaf individuals, particularly within the context of perceptual load theory. This question is crucial for understanding adaptive mechanisms and informing attention training interventions in the deaf population.MethodsTo investigate the impact of action video game experience on visual selective attention in deaf middle school students, a response competition paradigm combined with eye-tracking technology was employed to systematically evaluate and compare the selective attention characteristics of four groups: deaf action video game players (Deaf VGPs), deaf non-video game players (Deaf NVGPs), hearing action video game players (Hearing VGPs), and hearing non-video game players (Hearing NVGPs). The comparison was conducted under varying levels of perceptual load and types of distractors.Results(1) Deaf students generally demonstrated lower accuracy, slower reaction times, longer fixation durations, and more total fixation counts than their hearing counterparts in visual selective attention tasks. (2) Deaf VGPs performed better than deaf NVGPs, particularly in accuracy, and their performance in both accuracy and total fixation counts was comparable to that of their hearing counterparts, suggesting an association between action video game experience and enhanced selective attention in deaf students. (3) Deaf students, particularly NVGPs, exhibited larger compatible effects under both low and high perceptual load conditions, with the effect being more substantial under high load, indicating that perceptual load may exert a greater influence on deaf NVGPs.ConclusionThe mechanisms underlying selective attention processing in deaf students appear to be influenced by factors such as action video game experience and auditory deprivation-induced plasticity changes.